Meiosis I is established through division-specific translational control of a cyclin - Carlile, Thomas M. (2008)
In budding yeast key meiotic events such as DNA replication, recombination, and the meiotic divisions are controlled by Clb cyclin-dependent kinases (Clb-CDKs). Using a novel synchronization procedure, we have characterized the activity of these Clb-CDKs and observed a surprising diversity in their regulation during the meiotic divisions. Clb1-CDK activity is restricted to meiosis I, and Clb3-CDK activity to meiosis II through 5’UTR-mediated translational control of its transcript. The analysis of cells inappropriately producing Clb3-CDKs during meiosis I furthermore defines Clb3 as an inhibitor of the meiosis I chromosome segregation program. Our results demonstrate an essential role for Clb-CDK regulation in establishing the meiotic chromosome segregation pattern.